Die relatiewe belangrikheid van keuringskriteria soos waargeneem vanuit die oogpunt van verbruikersbankbestuurders - P. L.S. Ackermann; W. P.J. Van Rensburg (South African Journal of Business Management, 1985)
– The relative importance of evaluation criteria as observed by bank managers in consumer banking This study has the following objectives: (i) To determine the relative importance of various evaluation criteria (as observed by bank managers) in considering the granting of credit to individuals in consumer banking; and (ii) to compare the relative importance of evaluation criteria (as observed by bank managers) with regard to the various race groups (coloureds, Indians, whites, and blacks). The sample consists of 510 managers from the consumer division of general and commercial banks. It was found that significant differences exist regarding the relative importance of the evaluation criteria (according to the perception of bank managers) with respect to the various race groups.
Keywords: 650